Vibrações livres de viga de seção transversal variável - Oliveira, Carlos Frederico da Silveira (1969)
This work deals with the problem of the determination of the natural frequencies of transverse vibrations of beams of variable cross section, in particular beams with section heigh varying according to a polynbmial law. Ritz method is used for the determinátion of the natural frequencies, dueto its rapid convergence. The method of treatment of the problem, permits a determination of any of the natural frequencies using automatic programming because it does not limit the number of terms of the serie solution to be used.